Pandemic-era uncertainty on Main Street and Wall Street - Brent Meyer; Emil Mihaylov; Steven J. Davis; Nicholas Parker; David Altig; Jose Maria Barrero; Nicholas Bloom (Federal Reserve Bank of Atlanta, 2021)
We draw on the monthly Survey of Business Uncertainty (SBU) to make three observations about pandemic-era uncertainty in the U.S. economy. First, equity market traders and executives of nonfinancial firms share similar assessments about uncertainty at one-year lookahead horizons. That is, the one-year VIX has moved similarly to our survey-based measure of (average) firm-level subjective uncertainty at one-year forecast horizons. Second, looking within the distribution of beliefs in the SBU reveals that firm-level expectations shifted towards upside risk in the latter part of 2020. In this sense, decision makers in nonfinancial businesses share some of the optimism that seems manifest in equity markets. Third, and despite the positive shift in tail risks, overall uncertainty continues to substantially dampen capital spending plans, pointing to a source of weak growth in demand and in potential gross domestic product.
Keywords: L2; M2; O32; O33; 330; business expectations; uncertainty; subjective forecast distributions